Conserving procted areas and wildlife : a judicial journey - Enviro Legal Defence Firm (New Delhi, 2009)
The Centre for Environment Law (CEL) - WWF India was formally launched in 1993 and soon developed into an active centre for legal action through out the country. The Bhitarkanika case to protect the Olive Ridleys against an ecologically flawed jetty construction in Kendrapara, Orissa; the Narayan Sarovar Case against the Sanghi Cements Giant to save the Chinkara in the Narayan Sarovar Sanctuary in Gujarat and then an intervention in the Delhi ridge case in the early 90s have put CEL-WWF India at the forefront of fighting legal battles on wildlife conservation. The TRAFFIC India was equally active on fighting legal battles on specific illegal wildlife trade issues. It was around this time that the M.C. Mehta cases on various aspects of environment including river pollution, coastal areas, urban development were also at the peak of its judicial activism. It was then thought that a piece meal approach may not be the most appropriate manner to tackle wildlife conservation from the legal perspective. A preliminary research brought out that in most of the National Parks and Sanctuaries, the implementation of provisions as envisaged in the Wildlife Protection Act, 1972 (WLPA) is incomplete and therefore, it would be prudent to approach the Apex Court to ensure that the State Governments which were nodally responsible for managing the Protected Areas (PAs), expedite the process and inform the correct position of the Protected Area management in India. It was also felt that the status quo on this integral process is not benefiting either the conservation objectives or the social objectives. It is on this premise that the Civil Writ Petition No. 337 of 1995 was filed by CEL -WWF India in May, 1995 in the Supreme Court of India for the protection and development of the National Parks and Sanctuaries in India.
Keywords: Environment